Using Instagram to raise the effectiveness of distance learning in English: The experience of Kazakhstani students - Ramazanova, Dinara; Togaibayeva, Aigulden; Yessengulova, Meiramgul; Baiganova, Altynzer; Yertleuova, Baktygul (Frontiers in Education, 2022)
Despite the fact that social media are commonly considered entertaining means of communication, they have educational potential, which grants the teacher an opportunity to influence the learning process carried out in a distance format by means of a targeted system of pedagogical interventions. The problem of the study lies in the fact that in practice, the educational potential of social media is hardly ever used by teachers in Kazakhstan in spite of great opportunities to influence the process of students’ distance learning in the English language through a targeted system of measures, filling gaps in educational practice. The purpose of the study is to analyze the effectiveness of distance learning in the English language through the development and approbation of a teaching methodology using the Instagram social network. The main data collection methods used in the study are the survey method and a pedagogical experiment. Surveys of students and experts are employed in establishing the general appropriateness of using social media in educational activities in English lessons, as well as to assess the level of formation of students’ general and foreign language competencies. The pedagogical experiment method is used to analyze the effectiveness of social networks in the process of learning English. A method of organizing a thematic online marathon on Instagram is developed and experimentally tested by the authors. The study establishes that social media platforms can become a powerful tool for teaching contemporary students in the distance learning format if the teacher knows how to use their potential in educational work.